Dynamic Behavior of Rack Vehicle System Subject to Gravity Center Offset - YUAN, Mi'ao; CHEN, Zhaowei; LI, Shihui; CHEN, Zhihui; YANG, Jizhong (Mechanika (Kaunas, Lithuania : 1995), 2025)
During the operation of rack vehicles, gravity center offset is usually induced by the passenger distribution and the equipment layout, which greatly deteriorates the gear-rack dynamic meshing effect and the wheel/rail nonlinear friction contact behavior, and further threatens the safety and stability of the vehicle. Aiming at this problem, dynamic behavior of rack vehicle system subject to gravity center offset is investigated in this work. Considering the disturbance effect of gear-rack meshing impact and wheel/rail dynamic contact behavior, a complete dynamic model of rack vehicle is established based on multi-body dynamics, adopting which the influence of the carbody gravity center offset on the dynamic characteristics of rack vehicle and nonlinear meshing behavior of driven gear-rack system are explored. Results show that: The gear-rack dynamic contact force results in an impact under the rack vehicle carbody gravity center offset, and the impact increases with the increase of running speed. The gear-rack dynamic contact force reaches 73kN when the speed reaches 30km·h-1. The lateral offset of the gravity center has a linear effect on rack vehicle running safety, and the wheel/rail vertical force is affected by the gear-rack dynamic meshing and produce vibration. The rack vehicle running stability is more sensitive to the longitudinal offset of the gravity center. The carbody acceleration increases by 4.8 times when the carbody gravity center is 3.0m forward. The vertical Sperling index of the vehicle is optimal when the carbody gravity center is behind in 0~1 m. The conclusions of this study provide theoretical support for the worldwide rack railway design and safe operation.